Labour surplus and capital shortage: German unemployment in the first decade after the currency reform - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1987)
In the post-war economic history of West Germany, there have been two periods of significant unemployment. If we take full employment to mean a jobless rate of less than 3 %, the two periods can be dated as 1948 to 1958 and 1975 to the present. While the latter period has naturally been subject to extensive economic research and a passionate policy debate, the earlier one has long since been left as a playground for historians with their legitimate emphasis on fact-gathering and hindsight interpretation. In this paper, we shall take an economist's look at this first period of unemployment, i.e. we do not present - as historians would do - a rich menu of figures and documents which could have a chance of adding up to a complete historical picture; we rather select a bunch of descriptive statistical measures and contemporaneous academic analyses which yield a plausible economic explanation of the causes of and the remedies for the unemployment problem of the time. In detail, we proceed as follows. In Part 2, we give a brief quantitative outline of the level and the structure of West German unemployment in the fifties. In Part 3, we present the diagnosis of unemployment on which there was almost general agreement at the time and which still has much appeal today. While there was virtual consensus on the causes of unemployment, there was sharp disagreement on the remedies to be applied. In Part 4, we therefore present the most important paradigmatic views on economic policy as they appeared in the academic debate right at the time when unemployment reached its peak. In Part 5, we finally take a brief look at the path of economic policy which was actually pursued.
Keywords: 330; Kapitalmangel; Arbeitslosigkeit; Deutschland